Occurrence of electrostatic solitary waves in the lunar wake. Issue 9 (24th September 2017) - Rubia, R.; Singh, S. V.; Lakhina, G. S.
Abstract: An alternative generation mechanism for the electrostatic waves observed in the lunar wake during the first flyby of the Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) mission in terms of slow and fast ion‐acoustic and electron‐acoustic solitons is proposed. The lunar wake plasma is modeled by fluid multicomponent magnetized plasma comprising hot protons, hot heavier ions, α particles (He ++ ), electron beam, and suprathermal electrons following kappa distribution. The electric fields associated with the slow and fast ion‐acoustic and electron‐acoustic solitons are in the range of ∼(0.0003–17) mV m −1 . This is in excellent agreement with observed electrostatic wave electric field of 5 to 15 mV m −1 . The fast Fourier transform of soliton electric fields generates broadband spectra having peak frequencies (corresponding to peak in the power spectra) in the range of ∼(3–1800) Hz. This corresponds to wave frequencies being in the range of ∼(0.001–0.56) f pe, where f pe is the electron plasma frequency. This matches well with the observed frequency range of (0.01–0.4) f pe . Further, the widths and velocities of these solitons are in the range ∼(100–8000) m and ∼(30–1300) km s −1, respectively. Both, soliton widths and velocities, match well with the estimated wavelengths (a few hundred meters to a couple of thousand meters) and estimated phase velocities (of the order of 1000 km s −1 ) of the electrostatic waves in the lunar wake. Key Points: A soliton model for generation of electrostatic waves observed in the lunar wake during the first flyby of the ARTEMIS mission is proposed Slow and fast ion‐acoustic solitons and electron‐acoustic solitons can exist in the lunar wake Predicted amplitudes and frequency range of the electrostatic waves are in excellent agreement with lunar wake observations